Deletion mutation analysis of the region unique to the 289 residue protein from the ΕΠΑ region of adenovirus type 5 - Cunniff, Nina F. A. (My University, 1988)
The early gene region, EIA, of Adenovirus is responsible for two mRNAs that appear to be, along with their protein products, necessary for oncogenic transformation. The two proteins differ only in that the larger 289R protein has an extra internal sequence of 46 amino acids. This single difference must account for the functional differences between the two proteins. One function associated with this unique sequence is transactivation, the ability to transcriptionally activate the other early viral genes. In this thesis the construction and analysis of three in-frame deletion mutants are described. These three deletions, along with a fourth previously made, span the entire unique region. All three mutants had lost their transactivation ability, suggesting that the entire domain is necessary for transactivation. Transformation assays with these mutants also suggest that this function blocks transformation. Thus, the unique domain must encode another as yet unidentified function necessary for full transformation. Further evidence for another function in the unique domain comes from the differently reduced abilities of the mutants to grow on HeLa cells. Each mutant has differentially affected some function that is also necessary for lytic infection.
Keywords: Deletion Mutation Analysis